Essays on Political Economy - Rabelo, Alexandre Marcos Mendes (2022)
This thesis consists of two independent chapters. The first chapter aims to understand politicians’ careers, looking at the monetary and non-monetary outcomes of winning a mayoral election in Brazil. Specifically, we ask how becoming a mayor affects wage growth while in office and after the mayor mandate and other monetary dimensions such as firm ownership. Further, we investigate the impact of becoming a mayor on political career outcomes and occupational transitions in the formal labor market. To this end, we merged electoral data from 2004 to 2016 with a large administrative source of information and novel data on mayors’ wages to reconstruct politicians’ paths in political careers and the formal labor market. We estimate the effect of winning a municipal mayor election using a regression discontinuity design in a close election context. Our main finding is that the wage while in office represents a large wage growth for winners of mayoral elections when compared to the runners-up that were in the formal labor market after their loss in the elections. Since we find no effect on firm ownership and occupational mobility in the formal labor market, we interpret our results as evidence that the wage while in office is an important monetary benefit of becoming a mayor. To complement our analysis of a politician’s career, we also provide evidence that winning a close election for mayor election is not a gateway to other elective offices and does not increase the likelihood of future electoral wins. The second chapter studies the impact of a non-white mayor over the share of non-white managers in the municipal sector. The lack of non-white leadership has been pointed out as one of the potential drivers of the racial representation gap, especially in top positions. This study investigates the contribution of the race of the mayor to the racial representation gap in the context of the Brazilian public sector. Focusing on the 2016 Brazilian election, we use a regression discontinuity design to estimate the impact of electing a non-white mayor on a given municipality over the share of non-white municipal managers. We find that electing a non-white mayor is not associated with any significant increase in the share of non-white managers. We also discuss these results by exploring their relationship with the mayors’ networks, the municipalities’ racial policies, and the mayor’s party alignment.